Spontaneous tumor regression - Tarik Salman (Journal of Oncological Sciences, 2016)
Spontaneous tumor regression is defined as spontaneous remission or disappearance of a tumor in the absence of any treatment. Activation of immune system has been found important in its pathogenesis. Further, spontaneous tumor regression appears to be associated with apoptosis, tumor microenvironment, and DNA oncogenic suppression. It can be observed in all types of tumors, most frequently in renal cell cancer, germ cell tumors, malignant melanoma, and neuroblastoma. It is crucial to understand this phenomenon in order to improve the immune treatments which are effective in neoplastic diseases.